Validation of the organizational justice scale in a portuguese context - Abril, T.; Waldzus, S.; Collins, E. C. (The Psychologist-Manager Journal, 2020)
This article presents a Portuguese translation and cultural modification of the Organizational Justice Scale of Niehoff and Moorman (1993). The scale was tested in two correlational studies, one with 115 employees from the technical staff of a Portuguese organization and a second with 59 Portuguese teachers, testing the scale’s discriminant validity through comparison with other measures such as psychological contract violation, organizational identification, work motivation, job satisfaction and perceived ability–job fit. The scale showed satisfying consistency and in a factorial analysis of the Portuguese version; the item distribution per factor was the same as that of the original scale (Niehoff & Moorman, 1993). The Portuguese Organizational Justice scale showed adequate reliability and validity. Therefore, this Portuguese version can be considered a suitable instrument to assess organizational justice among the Portuguese population.